Islamic legal maxims for attainment of maqasid-al-shari‘ah in criminal law: reflections on the implications for Muslim women in the tension between Shari‘ah and western law - Zakariyah, Luqman (Springer, 2012)
The legal procedural system of Islamic criminal law has been criticised, either constructively or destructively, over a period of time. Some of the most recent cases in the twenty- fi rst century are the cases of Safiyyatu of Sokoto State and Amina of Kastina State of Nigeria respectively, who were convicted on adultery and later acquitted due to technical legal faults. One of the reasons for criticism of the two cases is based on the lack of incorporating the objective of Islamic Law through “intertextualizing” the textual evidence, on one hand, and on the other failure to extrapolate all sources available for “dynamizing” the Shari‘ah legal system. This chapter will address how these legal maxims can be explored to ensure that the purposes of Islamic criminal law are comprehended and that justice is established in Islamic legal procedure. In doing so, the two cases cited above will be used as empirical case studies. Some of the issues raised in the chapter are: Was criminal intention of the accused women considered? In other words, is it certain that the accused women intentionally committed the crime? Is there any shubha for giving them bene fi t of the doubt as required by law? Is it possible for someone to report a case of adultery to the authorities? Why were the two cases reported? Does retraction of a confession abate punishment of the accused? These questions will be answered through some relevant basic legal maxims of Islamic law which depict “maqasid al-Shari‘ah”.